Development of AERO® MX3048 Promoter for MMG Sepon Concentrator, South Central Laos - Peter Riccio; Tony Moore (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
"MMG (Minerals and Metals Group) operates the LXML Sepon’s mineral processing facility located 40 kilometers north of the town of Sepon, in the Savannakhet Province, Lao PDR. The Sepon copper plant produces 70,000 tons/year of LME grade A copper cathode using leachautoclave- SX/EW-flotation technology (Baxter et al., 2003). Pyrite recovery in the flotation circuit is critical to the operation, as it is used to generate acid and soluble ferric ion for the leach circuit. Low pyrite recovery has been an on-going challenge in the flotation circuit. Final tailings characterization work done by Ian Wark Research Institute (Bassell et al., 2006) showed that the pyrite losses to the tailings are made up of a combination of coarse liberated particles and finer particles that have been coated by clay fines.In December of 2005, a joint Cytec-MMG technical program was initiated to address the pyrite recovery issue. A series of diagnostic tests were performed in the Cytec Stamford Research Facility using synthetic plant water showing that the collector was precipitating as a metal salt and was unavailable for mineral attachment. The tests also identified several collector chemistries that would likely be robust in the low pH (< 1), high dissolved metal ion environment and will not complex with metal ions in solution. With the support of the Sepon on-site engineers, an extensive, successful laboratory program was completed, which was subsequently followed by on-plant testing that showed a step wise improvement in pyrite recovery.INTRODUCTIONLow pyrite recovery has been an ongoing problem in the flotation circuit at Sepon. Sulfur recovery (indirect measure of pyrite) was improved from 40% to 65%-75% in mid-2005 when on site laboratory work confirmed that AERO® 8045 Promoter was a more effective collector then AERO® 407 Promoter. However, sulfur recoveries above 65% could never be achieved. Sepon requested the Ian Wark Research Institute to complete a surface analysis study using Scanning Electron Microscopy, X-ray Photoelectron Spectroscopy, and Time-of-Flight Secondary Ion Mass Spectroscopy to determine if clay coated pyrite played a role. It was concluded that the pyrite losses to the tailings are made up of a combination of coarse (+ 100µm) liberated particles and finer (-74µm) particles that have been coated by clay fines. The majority of the losses appear to be due to the former. In December of 2005, a series of diagnostic tests were performed in Stamford using synthetic plant water in order to identify what chemistries would likely be robust in the slimy low pH and high dissolved metal ion solution environment. Results showed that several chemistries would not complex with ferric, ferrous or copper in solution and therefore should perform well in the Sepon flotation. The incumbent collector, AERO® 8045 Promoter was complexing with metal ions in solution. This resulted in the collector not being available for adsorption onto pyrite."